Working-time regulation, long hours working, overemployment and mental health - Otterbach, Steffen; Charlwood, Andy; Fok, Yin-King; Wooden, Mark (My University, 2021)
Using nationally representative panel data from Australia and Germany, this article investigates the relationships between working-time regulation, long working hours, overemployment and mental health, as measured by the Mental Component Summary score from the 12-item Short Form Health Survey (SF-12). Fixed effects and dynamic linear models are estimated, which, together with the longitudinal nature of the data, enable person-specific traits that are time invariant to be controlled for. Drawing on the Varieties of Capitalism literature it is hypothesized that the system of collective regulation of working time in Germany will be more effective in limiting the incidence of overemployment than the more individualized system of regulation in Australia so that the prevalence of working time related mental ill health is lower. Results do not support this hypothesis. Overemployment is similarly common in both countries and is also associated with lower levels of mental health in both countries.
International Journal of Human Resource Management
Keywords: Health and wellbeing; Labour market